Bringing automation to electromagnetic by robotic scanning of magnetic field in electric drives - Milanowski, Hubert; Piłat, Adam Krzysztof (Archives of Electrical Engineering, 2026)
Accurate magnetic field measurement is vital for analysing and optimizing electric machines such as permanent magnet synchronous motors. Existing methods struggle with complex geometries, enclosed structures, and multi-axis field variations.We propose a robotic arm-based system for automated, high-resolution scanning of all three magnetic field components across the full motor geometry, including stator and rotor. The system enables precise sensor positioning on curved surfaces for reliable data acquisition where traditional setups fail. Comprehensive spatial analysis, including harmonic decomposition, reveals hidden field patterns that support improved diagnostics and motor design. This flexible, scalable approach advances both experimental research and industrial evaluation of electric machines.